Waqf As A Tool to Address Poverty, Education, And Healthcare - Fazal-ur-Rehman, Alishba (AIBPM Publisher, 2024)
This paper explores the effective utilization of Waqf as a tool to address modern socio-economic challenges, specifically in poverty alleviation, education, and healthcare. Through a qualitative methodology, it examines historical and modern applications of Waqf, drawing on historical records, academic literature, and case studies, complemented by modern reports and statistics. The findings highlight that Waqf has historically supported key sectors, such as education, through the establishment of madrasas and modern institutions like Hamdard Medical University, and healthcare, with hospitals like. These institutions provided comprehensive services, showcasing Waqf’s ongoing contribution to poverty alleviation, education, and healthcare. However, the research notes that while Waqf holds significant potential, enhanced management, awareness, and legal reforms are crucial for maximizing its impact. The study fills a gap in current research by examining Waqf's modern influence and proposing practical solutions for its revitalization